2005
DOI: 10.1111/j.1462-2920.2005.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequent genetic recombination in natural populations of the marine cyanobacterium Microcoleus chthonoplastes

Abstract: A culture-independent method for multilocus sequence typing of Microcoleus chthonoplastes was developed based on mechanical separation of individual cyanobacterial filaments from natural microbial mat populations through micromanipulation, subsequent polymerase chain reaction (PCR) amplification and sequence analysis of three genetic loci (kaiC, petB/D, rDNA-ITS). Among 81 individuals sampled from intertidal sand flats of the North Sea and Baltic Sea, we found 8-14 different sequences (alleles) per genetic loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 33 publications
(44 reference statements)
1
29
0
Order By: Relevance
“…Phenotypic and phylogenetic analyses on 16S rRNA gene fragments done by Garcia-Pichel et al (1996) have shown that Microcoleus chthonoplastes is a cosmopolitan cyanobacterium. Interestingly, Lodders et al (2005) could provide the contrary, data on rRNA-ITS locus showed that this species sharing similar morphology differ on the genetic level. Similarly, Otsuka et al (2001) using the cpcBA intergenic spacer and 16S-23S internal transcribed spacer concluded that the six Microcystis morphospecies: M. aeruginosa, M. ichthyoblabe, M. novacekii, M. viridis, M. wesenbergii, M. flos-aquae and M. pseudofilamentosa, may possibly be unified into one species.…”
Section: Molecular Phylogeny Markers In Cyanobacterial Classificationmentioning
confidence: 85%
“…Phenotypic and phylogenetic analyses on 16S rRNA gene fragments done by Garcia-Pichel et al (1996) have shown that Microcoleus chthonoplastes is a cosmopolitan cyanobacterium. Interestingly, Lodders et al (2005) could provide the contrary, data on rRNA-ITS locus showed that this species sharing similar morphology differ on the genetic level. Similarly, Otsuka et al (2001) using the cpcBA intergenic spacer and 16S-23S internal transcribed spacer concluded that the six Microcystis morphospecies: M. aeruginosa, M. ichthyoblabe, M. novacekii, M. viridis, M. wesenbergii, M. flos-aquae and M. pseudofilamentosa, may possibly be unified into one species.…”
Section: Molecular Phylogeny Markers In Cyanobacterial Classificationmentioning
confidence: 85%
“…It clustered with subgroup B2 in protein phylogeny (in agreement with other phylogenomic reconstructions 13,25 but with group A in ribosomal phylogeny (in agreement with morphological and physiological data 31 , and exceptional domain acquisition of ValtRNA synthetases 32 ). Lodders et al provided evidence that genetic recombination in natural populations of the cyanobacterium M. chthonoplastes frequently occurs 33 and that the nitrogenase cluster has been horizontally acquired 34 .This highlights the complex evolutionary history of this strain in which massive gene acquisitions have recently been reported 25 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, some of the non-consistent phylogenetic signals of different gene families within the same bacterial species have been explained by HGT and HR (e.g. Hanage et al 2005;Lodders et al 2005;David and Alm 2011). It has been suggested that a part of the bacterial genome usually referred to as the core genome is more stable with less evolutionary changes.…”
Section: Speciation Factors In (Cyano)bacteriamentioning
confidence: 99%